Luangprabang hydropovver and its downstream accumulative impact on sedim ent flux - Hai, Nguyen Xuan; Huan, Nguyen Huu; Tuan, Nguyen Nhan (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 2, 2009)
Abstract